2009
DOI: 10.1080/07474930802467241
|View full text |Cite
|
Sign up to set email alerts
|

Instrumental Variables Estimation of Heteroskedastic Linear Models Using All Lags of Instruments

Abstract: We propose and evaluate a technique for instrumental variables estimation of linear models with conditional heteroskedasticity. The technique uses approximating parametric models for the projection of right-hand side variables onto the instrument space, and for conditional heteroskedasticity and serial correlation of the disturbance. Use of parametric models allows one to exploit information in all lags of instruments, unconstrained by degrees of freedom limitations. Analytical calculations and simulations ind… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(1 citation statement)
references
References 51 publications
0
1
0
Order By: Relevance
“…for our baseline estimates. Many authors have found optimally-weighted GMM procedures lead to biased estimates in small samples (e.g., Altonji and Segal, 1996;West et al, 2009). An important advantage of diagonal weighting matrices is that the contribution of each moment to q (θ, χ) can be easily computed.…”
Section: Two-stage Methods Of Simulated Momentsmentioning
confidence: 99%
“…for our baseline estimates. Many authors have found optimally-weighted GMM procedures lead to biased estimates in small samples (e.g., Altonji and Segal, 1996;West et al, 2009). An important advantage of diagonal weighting matrices is that the contribution of each moment to q (θ, χ) can be easily computed.…”
Section: Two-stage Methods Of Simulated Momentsmentioning
confidence: 99%